2016
DOI: 10.4028/www.scientific.net/amm.831.245
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental Investigation of Scroll Expanders Operating in the ORC System with HFE7100 as a Working Medium

Abstract: The paper presents the results of experimental investigation on the ORC system with a droplet separator (which was used to improve the quality of working medium vapour) and two scroll expanders, which operated individually. The research aimed at verifying the correctness of scroll expanders performance in the ORC installation, equipped with the electric flow heater for thermal oil as a heat source. The paper contains the characteristics of the heat exchangers installation that were obtained for the ORC system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It should be noted that different sources of information give different values (at a temperature of 65 • C) for the density and viscosity of the HFE7100 liquid and they differ by approx. 4.5% and 8%, respectively [5].…”
Section: Prototypical Rotor-jet Pumpmentioning
confidence: 97%
See 2 more Smart Citations
“…It should be noted that different sources of information give different values (at a temperature of 65 • C) for the density and viscosity of the HFE7100 liquid and they differ by approx. 4.5% and 8%, respectively [5].…”
Section: Prototypical Rotor-jet Pumpmentioning
confidence: 97%
“…This pump must be able to provide adequate pressure (1.2 MPa absolute pressure) and flow rate (0.17 kg/s) of the working fluid (HFE7100) at the inlet to an expansion machine. Based on the market analysis and measurements made [5], it was found that pumps that meet the above-mentioned criteria are not available. It should be noted that the HFE7100 fluid is a solvent, which considerably limits the possibility of using commercial pumps because of the potential damage to seals and structural elements of the pump (such as, for instance, shaft, bearings, impeller or body).…”
Section: Prototypical Rotor-jet Pumpmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotodynamic pumps can be used in many industries [5,15], due to their ability to work with so many different working mediums, throughout a wide operating range in terms of pressure and flow rate. Furthermore, they are perceived as highly reliable devices [3].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the requirements included in the Directive 2006/42/EC, the Ordinance of the Minister of Economy [49] and the Ordinance of the Minister of Labour and Social Policy [50], vibroacoustic tests of the two types of expansion devices were carried out, during their operation in the cogeneration ORC installation with the low-boiling working medium HFE7100. The following expansion devices were examined: 3 kW e prototypical four-stage radial microturbine [51] and 1 kW e commercial scroll expander [52,53].…”
Section: Introductionmentioning
confidence: 99%